Growth of B. Braunii-Andi-115 and Ch. Infusionum-Andi-76 Strains in Hoagland's Feed Medium and Zarruk Feed Medium (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article consists of studying the growth and development of B. braunii-AnDI-115 and Ch.infusionum-AnDI-76 strains in Hoagland's nutrient medium and zarruk nutrient medium, and the effect on the production of biomass and pigments in relation to dry matter.